Challenges of Memorandum of Understanding as a tool for strengthening intersectoral collaboration in health system - Behzad Damari; Narges Rostamigooran; Ali Asghar Farshad (Shahid Beheshti University of Medical Sciences, 2019)
ABSTRACT Background: For sustainable development and resolve complex public health problems intersectoral collaboration is a necessity. A MOU is one of the tools used to develop intersectoral interactions. In this study, the challenges in development and implementation  of MOUs and propose strategies to overcome these challenges were studied   through collecting the views of some stakeholders from other organizations . Method: For identifying challenges and  solutions to improve the situation, group discussions were conducted with the presence of representatives from four ministries of Agriculture, Roads and Urban Development, Sports and Youth, and Education and the representatives of the MoHME, who were responsible for preparing MoUs. All sessions were transcript and analyzed by using content analysis method. Results: Some challenges were defined according to development and implementation of MOUs . For better implementation ,suggested strategies were: Strengthening the stewardship of intersectoral collaboration, Effective and powerful management in monitoring the implementation of MOUs, Determining the appropriate financing path, Strengthening individual and organizational capabilities in developing and implementing of MoUs, Improving the terms and conditions of the implementing the MoUs.   Conclusion: Collaboration with other sectors has now become one of the main issues in health systems. For better achievement, strengthening the stewardship of intersectoral collaboration to effective coordination for drafting MoU, and facilitates and monitors the effective implementation of MoUs by identifying key people in each organization and empowering them is necessary.